Locutionary and Ilocutionary Act of Gibran Rakabuming Raka At The G20 Summit 2025 - Kafka Nabawi Suherman; Hanafi Wibowo; Ellis Tamela (Ekasakti Jurnal Penelitian dan Pengabdian, 2026)
This study aims to analyze the types of locutionary and illocutionary acts found in Gibran Rakabuming Raka’s speech at the 2025 G20 Summit and to explain how these speech acts are used in international political discourse. This research employed a qualitative descriptive method, and data were gathered from the official video and transcript of the speech using documentation, transcription, and coding procedures. A total of 28 utterances were analyzed at both locutionary and illocutionary levels, yielding 28 coded utterances per analytical layer. The data suggest that rhetic acts were the most prevalent locutionary acts (85.71%), indicating that the speech was mostly composed of meaningful propositions and informative utterances. Meanwhile, assertive acts were the most common illocutionary acts (53.57%), indicating that the speaker mostly articulated views, claims, and national positions on global concerns. The study suggests that Gibran employed speech actions strategically to attain informational, persuasive, and diplomatic communication objectives in the G20 conference.